Long live a historical study on the Mabuhay community newspaper in Bulacan - Agustin, Sir Lawrence Mendoza (2014)
"This study looked at how Mabuhay, the second oldest and still existing community newspaper in Bulacan, manages to survive for three decades. Its history was traced and the socioeconomic, political and cultural factors that affect its operations were determined. Through interviews with the people who work for Mabuhay as well as its readers, it aimed to know the reasons why it is still publishing and being read. From the data acquired from the in-depth interviews with its founders and workers, the researcher found that since 1980, Mabuhay faces problems such as the lack of funds, manpower, advertisements, and legal notice accreditation, among others. It was also discovered that Mabuhay focuses more on publishing environmental stories because of the impact such news have on Bulakenos. The community's recognition for the importance of local news despite being proximate to Metro Manila is also another reason why Mabuhay continuously publishes. The researcher also discovered that its readers perceive Mabuhay as perceived as a credible, truthful, and unbiased news source. The newspaper's content and the pleasant presentation of news (i.e.layout) is another factor why it is being read."